Combined radiation and immune checkpoint inhibitor therapy for metastatic or recurrent hepatocellular carcinoma: a real-world study of 108 patients - Yirui Zhai; Yefan Zhang; Fan Wu; Jianguo Zhou; Lingxia Xin; Feng Ye; Wei Sun; Huiying Zeng; Yan Song; Yongkun Sun; Wen Zhang; Shu-Lian Wang; et al. (Frontiers in Immunology, 2025)
BackgroundThe prognosis of metastatic or recurrent hepatocellular carcinoma (HCC) remains poor, and new treatment strategies are warranted. Despite promising preclinical results demonstrating that radiation primes the immune system and produces a synergistic antitumor response for long-term disease control, limited clinical data are available. Therefore, in this study, we investigated the efficacy and safety of combining radiotherapy with immune checkpoint inhibitors (ICIs) for patients with metastatic and recurrent HCC in a real-world setting.Materials and methodsPatients with stage IV or recurrent HCC who received sequential or concurrent radiotherapy and ICIs in our institution were enrolled in this study. Data regarding clinicopathological characteristics, treatment protocols, response rates, toxicities, and survival were collected.ResultsFrom January 2018 to December 2021, 108 patients were included. Extra-hepatic metastasis and portal vein tumor thrombosis were recorded in 58 (53.7%) and 69 patients (63.9%), respectively. A median radiation dose of 55 Gy was administered, and ICIs were administered for 3 weeks until disease progression or limiting toxicities occurred. After treatment, the overall response rate was 75.0%, and the median follow-up duration was 18.8 months. Median overall survival and progression-free survival were 17.0 and 12.6 months, respectively. Only one patient experienced in-field recurrence. Grade ≥3 adverse events were observed in 30.6% of patients. Dermatitis was the most common toxicity-related event and thrombocytopenia was the most common grade ≥3 adverse event, occurring overall in 17.6% of patients.ConclusionThe ICI and radiotherapy combination was effective and well-tolerated in real-world patients, achieving more favorable results compared with historical ones and providing a new multimodality therapy for patients with recurrent and metastatic HCC.